Behavioral Approaches in Overcoming Zoophobia: Modern Desensitization as a Revolutionary Therapy - Salsabila Nasution; Yeni Karneli (Jurnal Psikoedukasi dan Konseling, 2025)
Zoophobia, or excessive fear of animals, is a condition that can interfere with the daily lives of individuals who experience it. The purpose of this study will discuss the behavioral approach in overcoming zoophobia with a focus on modern desensitization as a revolutionary therapy.  The research method in this study uses a literature review study obtained from international and national articles and then analyzes the implementation of desensitization utilizing technology to overcome zoophobia. Through this method, individuals who experience zoophobia can gradually reduce their fear of animals in a structured and systematic way. Research shows that desensitization can significantly alleviate zoophobia. This article aims to provide a deeper understanding of the implementation of desensitization in overcoming zoophobia